Production of bacterial inoculant as biofertilizer and bioenhancer. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2003)
In Malaysia there are limited sources of bacterial inoculants as plant blofertlh2ers and bioenhancers. Plant growth-promoting rhizobacteria (PGPR) such as Azospirilium and Bacillus spp. can be safely used as inoculants to enhance plant growth, fix N2 and decrease enhance on Inorganic nitrogenous fertilizers. Several experiments were conducted to produce the inoculant namely the Isolation of bacteria, the carrier and its shelf life, and the efficacy on economic crops. higher acetylene-reduction assay (ARA) activities (129 umole plant-1 hour-1) and increased nutrient uptake.